Bacterial and microalgal communities in carp polyculture systems: Composition, affecting factors and further perspectives - Ngoc Minh Ngan Bui; Heyse, J.; Delamare-Deboutteville, Jerome; Defoirdt, T.; Props, R.; Shelley, Colin (Elsevier, 2024)
Carp polyculture is the planet's most widely practiced fish production system, using multiple fish species living in diverse trophic and spatial niches of a pond to maximize productivity. Increases in farm productivity can be supported by using healthy stock, more effective use of inputs (e.g., feed, probiotics, fertilizers), and improved disease management. However, there is a lack of understanding on how microbial–host interactions can help to avoid or manage dysbiosis in carp aquaculture systems to improve productivity. The availability of literature data derived from both traditional and new molecular techniques enables a comprehensive understanding of the diversity and functionality of the microbiota in carp polyculture systems. To support the development of improved best management practices for carp polyculture, we reviewed the current knowledge of microbiota in carp polyculture systems with a focus on bacteria and microalgae communities. This review highlights the link between the host microbiota and the rearing environment microbiota, thereby emphasizing its importance in steering the rearing water microbiota to reduce microbial dysbiosis in both the water and fish organs. Strong evidence implies that factors such as probiotics, prebiotics, feed, fertilizers, and manipulation of environmental parameters have a significant effect on carp microbiota. Development of management strategies towards three key areas (microbiome health assessment, technological improvements, and product management) are essential for the health of carp polyculture and will likely be critical for the industry's expansion.